2022
DOI: 10.1134/s0021364022040014
|View full text |Cite|
|
Sign up to set email alerts
|

Resonant Hybrid Metal–Dielectric Nanostructures for Local Color Generation

Abstract: Here, we experimentally and theoretically demonstrate a laser-induced change in local color based on the reshaping of gold–silicon asymmetric nanostructures. The evolution of scattering properties enabled by laser reshaping shows the potential of hybrid metal–dielectric nanostructures for color printing applications. The reshaping process can tune the resonance of the nanostructure in the wavelength range between 500 and 800 nm resulting in different colors of illuminated nanostructures. Moreover, the modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Zuev et al [ 12 ] demonstrated the fabrication of hybrid nanostructures with a magnetic optical response via femtosecond laser melting of asymmetrical metal–dielectric (Au/Si) nanoparticles created by lithographical methods. Furthermore, such asymmetrical hybrid nanostructures can be used to locally color the surface in a tunable way [ 13 ], as well as fano resonance [ 14 ] and near-field distribution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zuev et al [ 12 ] demonstrated the fabrication of hybrid nanostructures with a magnetic optical response via femtosecond laser melting of asymmetrical metal–dielectric (Au/Si) nanoparticles created by lithographical methods. Furthermore, such asymmetrical hybrid nanostructures can be used to locally color the surface in a tunable way [ 13 ], as well as fano resonance [ 14 ] and near-field distribution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%